Citizen Participation in the Information Society Comparing Participatory Channels in Urban Development - Hovik, Sissel; Giannoumis, G. Anthony; Reichborn-Kjennerud, Kristin; Ruano, José M.; McShane, Ian; Legard, Sveinung (Springer Nature, 2022)
This open access book examines how digital technologies are used to promote citizen participation in democratic urban development. It assesses the emergence, use, applicability and functions of digital modes of citizen participation in multiple cities around the world, where political regimes invite ordinary citizens to partake in policy processes through information technologies. The book also explores these initiatives alongside issues of democracy, social justice and power. It is an essential reference for practitioners, policymakers and academics interested in the relationship between citizen participation, technology and urban governance.